Investigations of the Emission Characteristics of a Dual-Fuel Gas Turbine Combustion Chamber Operating Simultaneously on Liquid and Gaseous Fuels - Serbin, Serhiy; Diasamidze, Badri; Gorbov, Viktor; Kowalski, Jerzy (My University, 2021)
This study is dedicated to investigations of the working process in a dual-fuel low-emission combustion chamber for a floating vessel’s gas turbine. As the object of the research, a low-emission gas turbine combustion chamber with partial premixing of fuel and air inside the outer and inner radial-axial swirls was chosen. The method of the research is based on the numerical solution of the system of differential equations which represent the physical process of mass and energy conservation and transformations and species transport for a multi-component chemically reactive turbulent system,considering nitrogen oxides formation and a discrete ordinates model of radiation. The chemistry kinetics is presented by the 6-step mechanism of combustion. Seven fuel supply operating modes, varying from 100% gaseous fuel to 100% liquid fuel, have been analysed. This analysis has revealed the possibility of the application of computational fluid dynamics for problems of dual-fuel combustion chambers for the design of a floating vessel’s gas turbine. Moreover,the study has shown the possibility of working in different transitional gaseous and liquid fuel supply modes, as they satisfy modern ecological requirements. The dependencies of the averaged temperature, NO, and CO concentrations along the length of the low-emission gas turbine combustion chamber for different cases of fuel supply are presented. Depending on the different operating modes, the calculated emission of nitrogen oxides NO and carbon monoxide CO at the outlet cross-section of a flame tube are different, but, they lie in the ranges of 31‒50 and 23‒24 mg/nm3 on the peak of 100% liquid fuel supply mode. At operating modes where a gaseous fuel supply prevails, nitrogen oxide NO and carbon monoxide CO emissions lie in the ranges of 1.2‒4.0 and 0.04‒18 mg/nm3 respectively.
Investigations of the Emission Characteristics of a Dual-Fuel Gas Turbine Combustion Chamber Operating Simultaneously on Liquid and Gaseous Fuels / S. Serbin, B. Diasamidze, V. Gorbov, J. Kowalski // Polish Maritime Research. – 2021. – Vol. 28. – P. 85–95.
Keywords: gas turbine engine; dual-fuel combustion; combustion chamber; liquid and gaseous fuels